Pembelajaran SKI Melalui Google Sites - Puadi, Hairul; Madarik, Muhammad (JURNAL PUSAKA, 2023)
In fact, the SKI (Islamic Cultural History) subject is somewhat shunned by most students. They viewed that SKI is a subject in the form of a set of "texts on history" which are more text-written so that they are considered boring, moreover the teacher's delivery still uses the traditional lecturing method. As a mover, the teacher should take steps to change in the classroom, including: [a] the teacher provides stimulation so that it does not dominate the teaching style; [b] students need to be given a wide space in the realm of creativity, so that they have the opportunity to think critically; [c] just as the government has made regulations on how the nation's generation can be more active, critical, and innovative in learning, educators are making efforts on how students are able to dominate the class; [d] one of the developments in the media domain is the use of Google tools. Google Sites is a tool for creating websites for teams, projects, events or other purposes. Through the use of Google Sites, the school community is designed to be able to present teaching materials, especially the SKI subject, in the form of more varied characteristics. The steps for using Google media include: [1] preparation before students access the Google Site; [2] activities while students access the Google Site. How to create Google Sites as stated in the Google guide. The Google Site provides teaching materials, and features that make learning effective. Key words: classroom; education; history; Islam; media learning